2010
DOI: 10.1111/j.1471-4159.2010.06653.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemopressins and other hemoglobin‐derived peptides in mouse brain: comparison between brain, blood, and heart peptidome and regulation in Cpefat/fat mice

Abstract: J. Neurochem. (2010) 113, 871–880. Abstract Many hemoglobin‐derived peptides are present in mouse brain, and several of these have bioactive properties including the hemopressins, a related series of peptides that bind to cannabinoid CB1 receptors. Although hemoglobin is a major component of red blood cells, it is also present in neurons and glia. To examine whether the hemoglobin‐derived peptides in brain are similar to those present in blood and heart, we used a peptidomics approach involving mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
3
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 58 publications
3
59
3
2
Order By: Relevance
“…In agreement with the original hypothesis that natural intracellular peptides have biological activity, the overexpression of the intracellular peptide metabolizing enzyme thimet oligopeptidase, which is known to alter the intracellular peptide profile in HEK293 cells (18), similarly changed angiotensin II and isoproterenol cell activation measured by the luciferase gene reporter assay (22). Taken together, these results suggest the exciting possibility that at least some of the naturally occurring intracellular peptides described here and elsewhere (19,20,36) may have biological activities similar to those previously described (22).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In agreement with the original hypothesis that natural intracellular peptides have biological activity, the overexpression of the intracellular peptide metabolizing enzyme thimet oligopeptidase, which is known to alter the intracellular peptide profile in HEK293 cells (18), similarly changed angiotensin II and isoproterenol cell activation measured by the luciferase gene reporter assay (22). Taken together, these results suggest the exciting possibility that at least some of the naturally occurring intracellular peptides described here and elsewhere (19,20,36) may have biological activities similar to those previously described (22).…”
Section: Discussionsupporting
confidence: 88%
“…All of the 92 peptides identified in the present study have also been identified in previous peptidomic studies using brain extracts from mice with distinctive genetic backgrounds, such as the BALB/C (19) and C57BKS/J (36). Altogether, these data suggest that mouse neuronal cells have a constant pool of intracellular peptides that is not related to MHC-I antigens.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…After incubation for 72 h at 37°C, cells were collected, washed four times in 30 ml of PBS by centrifugation for 5 min at 800 ϫ g at 4°C, and peptides extracted and labeled as described (31,32). Briefly, extracted peptides were labeled with five different 4-trimethylammoniumbutyryl isotopic labels (31,33). Duplicate samples treated with CCP1 siRNA were labeled with the D3-and D9-4-trimethylammoniumbutyryl, and triplicate control samples were labeled with D0-, D6-, and D12-4-trimethylammoniumbutyryl tags.…”
Section: Methodsmentioning
confidence: 99%